Expansion of bovine skeletal muscle stem cells from spinner flasks to benchtop stirred-tank bioreactors for up to 38 days - Tzimorotas, Dimitrios; Solberg, Nina Therese; Andreassen, R. Christel; Moutsatsou, Panagiota; Bodiou, Vincent; Pedersen, Mona Elisabeth; Rønning, Sissel Beate (Frontiers in Nutrition, 2023)
Successful long-term expansion of skeletal muscle satellite cells (MuSCs) on a large scale is fundamental for cultivating animal cells for protein production. Prerequisites for efficient cell expansion include maintaining essential native cell activities such as cell adhesion, migration, proliferation, and differentiation while ensuring consistent reproducibility. This study investigated the growth of bovine MuSC culture using low-volume spinner flasks and a benchtop stirred-tank bioreactor (STR). Our results showed for the first time the expansion of primary MuSCs for 38 days in a bench-top STR run with low initial seeding density and FBS reduction, supported by increased expression of the satellite cell marker PAX7 and reduced expression of differentiation-inducing genes like MYOG, even without adding p38-MAPK inhibitors. Moreover, the cells retained their ability to proliferate, migrate and differentiate after enzymatic dissociation from the microcarriers. We also showed reproducible results in a separate biological benchtop STR run.